Collaborative online international learning (COIL) on Laudato Si’: Ecuador and Argentina campaigning together - Yepez-Reyes, Veronica; Mettini, Gabriel Danilo; López-Paredes, Marco (Journal of International Students, 2026)
The concept of Integral Ecology, introduced in Laudato Si’, highlights the interdependence of humanity, society, and nature, calling for shared global responsibility and sustainable lifestyles. In this context, forty-six communication students and four professors from Ecuador and Argentina participated in a six-week collaborative online international learning (COIL) project, “University Laudato Si’” (2023), integrating the service learning (SL) methodology. Participants were able to co-design and implement an international sustainability campaign adapted to diverse cultural and social contexts. The study adopts a qualitative design, analyzing students’ videos, final presentations, and written reflections. This triangulation identified learning outcomes and collaborative dynamics in both international and local campaigning. The findings indicate that international teamwork enhanced participation, interaction, and intercultural understanding while empowering students to assume leadership roles as promoters of global citizenship committed to sustainability and social responsibility.